Open prison architecture: design criteria for a new prison typology - Vessella, Luigi (WIT Press, 2017)
As a part of the debate on penitentiary architecture, this book proposes a critical interpretation of the conceptual elements and design approaches involved. This proposal, more than others, may "mend" the relationship between theoretical conception and the actual building practice for a prison